Investigating the relationship between IT capability and organizational performance: An empirical evidence from Indian banking units - Sukanya Panda; Santanu Kumar Rath (The International Journal of Management Science and Information Technology (IJMSIT), 2015)
The purpose of this paper is to empirically analyze the effect of information technology (IT) capability on organizational performance through a resource based view (RBV). Primary data collected from 50 IT executives and 250 managers are used for this study and multiple linear regression (MLR) is employed to assess the link between IT capability dimensions (IT knowledge, IT objects, and IT operations) and organizational performance. This study concludes that IT capability has a significant positive relationship with organizational performance. This study is relevant to IT literature as it contributes a thorough analysis on key dimensions under IT capability that represent a significant link with organizational performance.
Keywords: 650; IT capability; resource based view; multiple linear regression; organizational performance